G425(P) A systematic review and meta-analysis of out of hospital nursing interventions to reduce emergency department attendances in children and young people. (12th March 2018) - Satherley, R; Lonergan, K; Devakumar, D; Cheung, R; Cortina-Borja, M; Heys, M; Wolfe, I
Abstract : Aims: Rising use of emergency departments has resulted in increased costs and poor quality of care for children and young people. Clear evidence on which interventions work in reducing the number of unplanned admissions is important for those who use and commission emergency department services and to improve the quality of healthcare services. There is a policy imperative to shift care out of hospitals but insufficient evidence on the effectiveness of out of hospital care. This review aims to identify, critique, and collate outcomes in published evidence for nurse-led out hospital care for children and young people with chronic conditions. Methods: Two databases were systematically searched from 1965–2017, to identify randomised controlled trials that used nurse-led out of hospital care to reduce emergency department attendances in children and young people (0–18 years) with at least one chronic condition. The pooled incidence rate ratio (IRR) was estimated using the R package metaphor. Results: Five randomised controlled trials (3 USA, 1 Canada, 1 Scotland) met the inclusion criteria. All five trials were included in the qualitative review but four were included in the meta-analysis due to heterogeneity in outcome measures. Four papers reported on CYP with asthma and the fifth on chronic illness. Only three papers reported significant effect for a reduction in emergency department attendances. Study quality was moderate, with a medium risk of bias. The meta-analysis fitted a random-effects model, which estimated a pooled IRR of 0.65 (95% CI 0.40, 1.03) implying a non-significant positive effect of nurse-led out of hospital care on reducing emergency department attendance. Conclusions: Although this review found no association between emergency department usage and nurse-led out of hospital care, the effect sizes were large and three papers found positive associations. Only five randomised controlled trials were included in this review, most of which studied children and young people with asthma, highlighting the need for further research in this area.